Surface plasmon resonance sensor with a magneto-optical structure - Pistora, Jaromir; Lesnak, Michal; Vlasin, Ondrej; Cada, Michal (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Due to resonant excitation of surface plasmons, surface plasmon resonance (SPR) sensors combined with ferromagnetic thin films allow an enhancement of the magneto-optical (MO) response. MO-SPR structures with Au/Co/Au sandwiches are theoretically analyzed in transverse configuration by 4×4 matrix algebra. The influence of sandwich film thickness, layer order and Co–Au multilayers on the relative change of the reflectance for p-polarized waves is analyzed. The results show the important role of the incidence angle distribution of the reflectance without magnetic ordering on the MO-SPR response. An optimized geometry and a corresponding feedback are discussed.
Optica Applicata, Vol. 40, 2010, nr 4, s. 883-895
Keywords: optyka; surface plasmon resonance; magneto-optics; induced anisotropy; optical sensors